2009
DOI: 10.1248/bpb.32.237
|View full text |Cite
|
Sign up to set email alerts
|

Goshuyuto, a Traditional Japanese Medicine, and Aqueous Extracts of Evodiae Fructus Constrict Isolated Rat Aorta via Adrenergic and/or Serotonergic Receptors

Abstract: Effects of goshuyuto, a traditional Japanese medicine, on vascular constriction were examined using isolated strips of rat aorta. Goshuyuto (1؋10 ؊5 to 1؋10 ؊3 g/ml) caused constriction of aorta strips in a dose-dependent manner. The vasoconstrictive effects of goshuyuto were significantly inhibited by pretreatment with prazosin, an adrenergic a a 1 receptor antagonist. The constrictive effects were partially inhibited by pretreatment with BRL15572, a 5-HT 1D antagonist, and ketanserin, a 5-HT 2A antagonist. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…It was observed that reserpine-induced migraine headache attacks are associated with excessive catecholamine metabolism (30), therefore, a disturbance of catecholamine metabolism is important in migraines. In addition, meningeal noxious stimulation activates the primary sensory trigeminal fibers, resulting in the release of calcitonin gene related peptide, and endogenous NO is involved in this process (31). The catecholamines, 5-HT, NE, DA, and vasoactive substances, NO, NOS are associated with the modeling mechanism and can visually reflect the pathophysiological characteristics of models, thus, they are selected as pharmacodynamic indices.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that reserpine-induced migraine headache attacks are associated with excessive catecholamine metabolism (30), therefore, a disturbance of catecholamine metabolism is important in migraines. In addition, meningeal noxious stimulation activates the primary sensory trigeminal fibers, resulting in the release of calcitonin gene related peptide, and endogenous NO is involved in this process (31). The catecholamines, 5-HT, NE, DA, and vasoactive substances, NO, NOS are associated with the modeling mechanism and can visually reflect the pathophysiological characteristics of models, thus, they are selected as pharmacodynamic indices.…”
Section: Discussionmentioning
confidence: 99%
“…Goshuyuto (TJ-31) is composed of four herbal components. In basic research, goshuyuto inhibits platelet aggregation in guinea-pig whole blood [ 18 ] and constricts the isolated rat aorta [ 19 ]. These findings suggested that goshuyuto decreases platelet hyper-aggregation, preventing excess serotonin release.…”
Section: Discussionmentioning
confidence: 99%
“…Goreisan (TJ-17) may activate the glymphatic flow correctly and promote the drainage of inflammatory substances by regulating the aquaporin 4 channel, thereby suppressing the headache [ 12 , 13 ]. Goshuyuto (TJ-31) may adjust serotonin levels and vessel constriction appropriately [ 14 , 15 ], and raising serotonin levels beforehand by goshuyuto [ 16 ] may suppress the hyper-reactivity of serotonin receptors for serotonin, leading to the prevention of migraine attack. Kakkonto (TJ-1) may relieve tension-type headaches by upregulating blood flow in the shoulder muscles [ 17 ].…”
Section: Discussionmentioning
confidence: 99%